2000
DOI: 10.1128/jb.182.11.3210-3218.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Genotypes ofHelicobacter pylorifrom Different Human Populations

Abstract: DNA motifs at several informative loci in more than 500 strains of Helicobacter pylori from five continents were studied by PCR and sequencing to gain insights into the evolution of this gastric pathogen. Five types of deletion, insertion, and substitution motifs were found at the right end of the H. pylori cag pathogenicity island. Of the three most common motifs, type I predominated in Spaniards, native Peruvians, and Guatemalan Ladinos (mixed Amerindian-European ancestry) and also in native Africans and U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
269
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(286 citation statements)
references
References 55 publications
13
269
1
2
Order By: Relevance
“…These associations between markers in H. pylori housekeeping gene sequences and geographical origin were in agreement with other reports that East Asian isolates had independent virulence-associated genotypic features -for instance, the type II cag right-junction motif was present in 95 % of East Asian strains compared to 1 % or less of strains from Africa, North America and South Asia (Kersulyte et al, 2000). Moreover, independent cag pathogenicity-island-related evidence that East Asian strains may constitute a genetically distinct population was provided by analysis of the 59 region of cag A (Yamaoka et al, 1998), of other regions of cagA (van der Ende et al, 1998) and of the right end of the cag pathogenicity island (Kersulyte et al, 2000), as well as by presence of the vacA s1c subtype allele as an East Asian strain marker (van Doorn et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…These associations between markers in H. pylori housekeeping gene sequences and geographical origin were in agreement with other reports that East Asian isolates had independent virulence-associated genotypic features -for instance, the type II cag right-junction motif was present in 95 % of East Asian strains compared to 1 % or less of strains from Africa, North America and South Asia (Kersulyte et al, 2000). Moreover, independent cag pathogenicity-island-related evidence that East Asian strains may constitute a genetically distinct population was provided by analysis of the 59 region of cag A (Yamaoka et al, 1998), of other regions of cagA (van der Ende et al, 1998) and of the right end of the cag pathogenicity island (Kersulyte et al, 2000), as well as by presence of the vacA s1c subtype allele as an East Asian strain marker (van Doorn et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…Differences in the consequences of colonization could depend on variation among colonizing H. pylori strains, on environmental cofactors, or on factors determined by the individual host. In particular, DNA-level analyses have indicated that H. pylori is one of the most genetically diverse of bacterial species (3,7,8).…”
Section: H Pylori and Illness In Humansmentioning
confidence: 99%
“…Several reports have evidenced geographical differences in the prevalence of vacA alleles and cagA status among H. pylori isolates (Kersulyte et al 2000, Catalano et al 2001, Valmaseda-Perez et al 2001; however, there is limited information about H. pylori infection in the countries of the Caribbean basin. The aim of this study was to determine the frequency of different H. pylori cagA/vacA genotypes among patients with chronic gastritis in Cuba and Venezuela.…”
mentioning
confidence: 99%
“…105(3): 331-335, May 2010 Helicobacter pylori is a microaerophilic bacterium that has the ability to establish an infection in human stomachs that can last for years or even decades, despite immune and inflammatory responses and the normal turnover of the gastric epithelium in which it resides (Kersulyte et al 2000). Infection with this microorganism is not only the major cause of chronic active gastritis and most peptic ulcer diseases, but it is also associated with gastric cancers (Blaser & Berg 2001).…”
mentioning
confidence: 99%